The Effect of Sentencing Reform on Racial and Ethnic Disparities in Involvement with the Criminal Justice System: The Case of California's Proposition 47 - Magnus Lofstrom; Brandon Martin; Steven Raphael (Institute of Labor Economics (IZA), 2019)
We analyze the disparate effects of a recent California sentencing reform on the arrest, booking, and incarceration rates experienced by California residents from different racial and ethnic groups. In November 2014 California voters passed state proposition 47 that redefined a series of felony and "wobbler" offenses (offenses that can be charged as either a felony or misdemeanor) as straight misdemeanors, causing an immediate 15 percent decline in total drug arrests, an approximate 20 percent decline in total property crime arrests, and shifts in the composition of arrests away from felonies towards misdemeanors. Using microdata on the universe of arrests in the state in conjunction with demographic data from the American Community Survey, we document a substantial narrowing in inter-racial differences in overall arrest rates and arrest rates by offense type, with very large declines in the inter-racial arrest rate gaps for felony drug offenses. Conditional on being arrested, we see declines in bookings rates for all groups, though we find a larger decrease for white arrestees. This relatively larger decline for white arrests is largely explained by difference in the distribution of arrests across recorded offenses. Despite the widening of racial gaps in the conditional booking rate, we observe substantial declines in overall booked arrests that are larger for African Americans and Hispanics relative to whites. For some offenses (felony drug offenses), inter-racial disparities in jail booking rates narrow by nearly half. Finally, we use data from the American Community Survey to analyze change in the proportion incarcerated on any given day and how these changes vary by race and ethnicity. For these results, we present trends for the time period spanning the larger set of policy reforms that have been implemented in the state since 2011. We observe sizable declines in the overall incarceration rate for African Americans, with the largest declines observed for African America males. The one-quarter decline in total correctional populations in the state coincided with sizable narrowing in inter-racial difference in incarceration rates.
Keywords: K40; K42; 330; racial disparity; criminal justice; reform; arrests; incarceration; Proposition 47